1997
DOI: 10.1111/j.1440-1754.1997.tb01606.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed umbilical cord clamping in preterm infants: A feasibility study

Abstract: A 30 s delay in cord clamping is feasible at both vaginal and Caesarean births, but does not lead to the predicted difference in infant haematocrit. Although physiological studies suggest that a placental transfusion of 15-20 mL/kg occurs within 30 s of delivery, these data suggest that future trials should either delay cord clamping for more than 30 s, or should alter the position of the infant in relation to the uterus in order to facilitate the transfusion. Delayed cord clamping is feasible at Caesarean sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
2
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 9 publications
(3 reference statements)
2
83
2
1
Order By: Relevance
“…This may deprive neonates of significant blood volume and can cause neonatal short-term and long-term potential problems such as respiratory distress, anemia and cerebral pulsy and mental retardation. 2,3 Benefits associated with delayed clamping include better cardiopulmonary adaptation, prevention of respiratory distress, prevention of anemia in infancy and increased duration of early breastfeeding. [4][5][6] The concerns regarding delayed cord clamping include the possibility of precipitating polycythemia, hyperviscosity, hyperbilirubinemia and transient tachypnea of the newborn.…”
Section: Introductionmentioning
confidence: 99%
“…This may deprive neonates of significant blood volume and can cause neonatal short-term and long-term potential problems such as respiratory distress, anemia and cerebral pulsy and mental retardation. 2,3 Benefits associated with delayed clamping include better cardiopulmonary adaptation, prevention of respiratory distress, prevention of anemia in infancy and increased duration of early breastfeeding. [4][5][6] The concerns regarding delayed cord clamping include the possibility of precipitating polycythemia, hyperviscosity, hyperbilirubinemia and transient tachypnea of the newborn.…”
Section: Introductionmentioning
confidence: 99%
“…The trial in which infants were not lowered failed to show placental transfusion. 8 In the trial with a clamping delay of 1-2 minutes the infants were also not lowered, but the longer delay was sufficient for placental transfusion. 24 …”
Section: >10 CM Abovementioning
confidence: 99%
“…6 The haematological effects of delayed cord clamping in preterm infants were studied in four randomised controlled trials from industrialised countries. [7][8][9][10] The observation period lasted four to six weeks and comprised the time the infants were admitted to the neonatal intensive care unit. Many of these infants born before 30 weeks of gestation would not have…”
Section: Is Delayed Cord Clamping Associated With Improved Haematologmentioning
confidence: 99%
“…2 The lack of benefit could reflect the lack of adequate placental transfusion during DCC for infants delivered by cesarean delivery (CD). [3][4][5] Three trials of DCC that stratified by mode of delivery found no difference in hematocrit levels or tagged red blood cells in infants delivered by CD. [3][4][5] The ACOG statement acknowledges that there are limited data indicating whether DCC performed during CD can improve placental transfusion.…”
Section: What This Study Addsmentioning
confidence: 99%
“…[3][4][5] Three trials of DCC that stratified by mode of delivery found no difference in hematocrit levels or tagged red blood cells in infants delivered by CD. [3][4][5] The ACOG statement acknowledges that there are limited data indicating whether DCC performed during CD can improve placental transfusion. 1 An alternative to DCC is umbilical cord milking (UCM), or stripping, in which the unclamped umbilical cord is grasped and blood is pushed toward the infant several times before it is clamped to autoinfuse blood into the preterm neonate.…”
Section: What This Study Addsmentioning
confidence: 99%